Introduction to clinical psychology : bridging science and practice - Bernstein, Douglas A.; Teachman, Bethany A.; Olatunji, Bunmi O.; De Los Reyes, Andres (Cambridge, UK : Cambridge University Press, 2025)
"Thoroughly revised, the tenth edition of this bestselling textbook introduces students to clinical psychology as a bridge between science and practice. Ideal for advanced undergraduate and graduate students, this pedagogically rich textbook teaches its readers to think critically, consolidate their learning , and stay up-to-date in the field."
Includes bibliographical references and index.
Keywords: Clinical psychology; Psychology, clinical